AMBIGUITY IN SONG LYRICS OF THE BEST DAY BY TAYLOR SWIFT - Pratiwi, Imas Meilisa Dewiworo (Program Studi Pendidikan Bahasa Indonesia, Institut Pendidikan Nusantara Global, 2023)
The purpose of this study is to identify ambiguity in the lyrics of the song entitled